The War Within Preventing Suicide in the U.S. Military - Ramchand, Rajeev (RAND Corporation, 2011)
The increase in suicides among military personnel has raised concern. This book reviews the current evidence on suicide epidemiology in the military, identifies state-of-the-art suicide-prevention programs, describes and catalogs suicide-prevention activities in the U.S. Department of Defense (DoD) and across each service, and recommends ways to ensure that the activities in DoD and across each service reflect state-of-the-art prevention science.